H2O2-independent chemodynamic therapy initiated from magnetic iron carbide nanoparticle-assisted artemisinin synergy. Issue 59 (22nd November 2021) - Zhao, Fan; Yu, Jing; Gao, Weiliang; Yang, Xue; Liang, Liying; Sun, Xiaolian; Su, Dan; Ying, Yao; Li, Wangchang; Li, Juan; Zheng, Jingwu; Qiao, Liang; et al.
Abstract : Chemodynamic therapy (CDT) is a booming technology that utilizes Fenton reagents to kill tumor cells by transforming intracellular H2 O2 into reactive oxygen species (ROS), but insufficient endogenous H2 O2 makes it difficult to attain satisfactory antitumor results. Abstract : Chemodynamic therapy (CDT) is a booming technology that utilizes Fenton reagents to kill tumor cells by transforming intracellular H2 O2 into reactive oxygen species (ROS), but insufficient endogenous H2 O2 makes it difficult to attain satisfactory antitumor results. In this article, a H2 O2 -free CDT technique with tumor-specificity is developed by using pH-sensitive magnetic iron carbide nanoparticles (PEG/Fe2 C@Fe3 O4 NPs) to trigger artemisinin (ART) to in situ form ROS. ART-loaded PEG/Fe2 C@Fe3 O4 NPs are fabricated for the enormous release of Fe 2+ ions induced by the acidic conditions of the tumor microenvironment after magnetic-assisted tumor enrichment, which results in the rapid degradation of the PEG/Fe2 C@Fe3 O4 NPs and release of ART once endocytosed into tumor cells. In situ catalysis reaction between the co-released Fe 2+ ions and ART generates toxic ROS and then induces apoptosis of tumor cells. Both in vitro and in vivo experiments demonstrate that the efficient Fe-enhanced and tumor-specific CDT efficacy for effective tumor inhibition based on ROS generation. This work provides a new direction to improve CDT efficacy based on H2 O2 -independent ROS generation.